2022
DOI: 10.1186/s40662-022-00286-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography metrics in different stages of diabetic macular edema

Abstract: Background To investigate the optical coherence tomography angiography (OCTA) characteristics of diabetic macular edema (DME) at different stages. Methods This study was a cross-sectional study. Patients diagnosed with DME were recruited. DME was classified into early, advanced, and severe DME. The vessel density (VD) in the superficial vascular plexus (SVP), deep vascular plexus (DVP) and foveal avascular zone (FAZ) parameters, including FAZ area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(39 reference statements)
0
5
0
2
Order By: Relevance
“…Many DME-related biomarkers based on SD-OCT imaging, such as CST, choroidal thickness, HRD, HE, SRF, IRC, EZ or ELM rupture, and DRIL, have been proven to be general prognostic biomarkers of anatomical or functional outcomes [ 16 – 20 ]. In the future, the information parameters of macular perfusion provided by OCTA will be further used in the evaluation system [ 21 ]. A large amount of HRD predicts a slight reduction in CST after anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many DME-related biomarkers based on SD-OCT imaging, such as CST, choroidal thickness, HRD, HE, SRF, IRC, EZ or ELM rupture, and DRIL, have been proven to be general prognostic biomarkers of anatomical or functional outcomes [ 16 – 20 ]. In the future, the information parameters of macular perfusion provided by OCTA will be further used in the evaluation system [ 21 ]. A large amount of HRD predicts a slight reduction in CST after anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Differences were also noted regarding the OCTA quantitative parameters in patients with DME of different grades of severity [ 34 ]. It was concluded that patients with severe DME presented lower perfusion in the DVP, compared to early and advanced DME [ 34 ].…”
Section: Quantitative Octa Assessment In Diabetic Macular Edemamentioning
confidence: 99%
“…Son zamanlarda kullanımı giderek artan OKT-anjiyografi (OKTA) de yüzeyel ve derin kapiller pleksusun değerlendirmesini girişimsel olmayan bir şekilde yaparak, ameliyat öncesi maküler iskemiyi belirleyebilir ve cerrahi sonrası maküler iskemiye bağlı kötü görsel prognozu değerlendirmede yardımcı olabilir. [2] Han Rui ve ark, [21] 92 DMÖ'lü gözü kapsayan kesitsel çalışmalarında, OKTA ile değişen evrelerde DMÖ'lü gözlerde vasküler parametreleri incelemişler; DMÖ ciddiyeti, FAZ alanı ve fovea kalınlığı ile kötü GK arasında korelasyon olduğunu saptamışlardır. OKTA ile, DMÖ'nün şiddeti arttıkça derin kapiller pleksusta vasküler yoğunlukta azalma ve FAZ' da düzensizliğin artarak genişlediği gösterilmiştir.…”
Section: Diyabetik Maküla öDeminin Patofizyolojisi Ve Etki Mekanizmasıunclassified
“…OKTA ile, DMÖ'nün şiddeti arttıkça derin kapiller pleksusta vasküler yoğunlukta azalma ve FAZ' da düzensizliğin artarak genişlediği gösterilmiştir. [21] DRCR.net Protokol I'nın alt analizinde, Anti-VEGF tedavisinin etkili olduğu, GK' de belirgin iyileşme olan DMÖ'lü hastaların, daha genç yaşta, daha az şiddetli DR'si olan ve arayüzey problemi olmayan hastalar olduğunu belirtilmiştir. [22] Bu sonuçları temel alarak vitrektominin özellikle yaşlı, daha şiddetli DR'si olan ve yüzey kırışıklığı olan DMÖ'lü hastalarda bir tedavi seçeneği olabileceği bildirilmiştir.…”
Section: Diyabetik Maküla öDeminin Patofizyolojisi Ve Etki Mekanizmasıunclassified